Executive Committee Minutes 2009-08-27 - Academic Senate:::::::::
Proposal for Faculty Governance Release Time '09 – '10, Proposal to leverage technology to reduce copy costs to the Senate budget, Faculty Eligible for Emeritus Status, Resolution on Priority for Reports at the Senate